Preliminary Study on the Effect of Inlet Pressure of Standard Slit Interdigital Micro Mixer Towards Mixing by Computational Fluid Dynamics - Termizi, Siti Nor Azreen Ahmad; Shukor, Syamsul Rizal Abd. (Taylor's University, 2014)
The aim of this work is to visualise the velocity profile and concentration profile of the mixing element of standard slit interdigital micro mixer (SSIMM) by simulating it in computational fluid dynamic (CFD). Since the micro mixer uses pressuredriven flow as its fluid actuation, the effect of change of the inlet pressure towards these profiles is observed. These preliminary study would give the general overview of the properties of the mixing element which will contribute to further studies later on in the mixing performance of this type of micro mixer.